2005
DOI: 10.1103/physrevd.72.115009
|View full text |Cite
|
Sign up to set email alerts
|

Electric dipole and magnetic quadrupole moments of theWboson via aCP-violatingHWWvertex in effective Lagrangians

Abstract: The possibility of nonnegligible W electric dipole ( W ) and magnetic quadrupole (Q W ) moments induced by the most general HWW vertex is examined via the effective Lagrangian technique. It is assumed that new heavy fermions induce an anomalous CP-odd component of the HWW vertex, which can be parametrized by an SU L 2 U Y 1-invariant dimension-six operator. This anomalous contribution, when combined with the standard model CP-even contribution, leads to CP-odd electromagnetic properties of the W boson, which a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 36 publications
3
56
0
Order By: Relevance
“…It was shown that the most general HW W coupling, which includes both CP-even and CP-odd components, can give rise to both CP-odd W W γ form factorsκ andQ. The numerical estimates obtained for appropriate values of the unknown parameters are µ W ∼ 3 − 6 × 10 −20 e· cm and Q W ∼ −10 −36 e· cm 2 [28]. We thus can conclude that the values for µ W and Q W induced by the anomalous tbW coupling, which are about 7 and 17 orders of magnitude above their respective SM predictions, are one order of magnitude smaller that those generated by an anomalous HW W coupling.…”
Section: The Edm Of the W Bosonmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that the most general HW W coupling, which includes both CP-even and CP-odd components, can give rise to both CP-odd W W γ form factorsκ andQ. The numerical estimates obtained for appropriate values of the unknown parameters are µ W ∼ 3 − 6 × 10 −20 e· cm and Q W ∼ −10 −36 e· cm 2 [28]. We thus can conclude that the values for µ W and Q W induced by the anomalous tbW coupling, which are about 7 and 17 orders of magnitude above their respective SM predictions, are one order of magnitude smaller that those generated by an anomalous HW W coupling.…”
Section: The Edm Of the W Bosonmentioning
confidence: 99%
“…Beyond the SM, most of the studies have focused on µ W , with the exception of Ref. [28], in which both µ W and Q W were estimated. In sharp contrast with the negligibly small SM predictions, some of its extensions predict values several orders of magnitude larger.…”
Section: The Edm Of the W Bosonmentioning
confidence: 99%
See 2 more Smart Citations
“…Along these lines, in Ref. [1] we calculated the one-loop contributions to the W W V * vertex from the gauge sector of the so called minimal 331 model [15,16]. In order to construct a well-behaved gauge independent Green function, rather than using the PT, we invoked an alternative method inspired in the BFM and BRST symmetry [17], which is well suited to study the sensitivity of the W W V * vertex to the virtual effects of the new gauge bosons predicted by 331 models.…”
Section: Introductionmentioning
confidence: 99%